Financial development and openness : evidence from panel data. - Baltagi, Badi H.; Demetriades, Panicos O.; Law, Siong Hook (Elsevier, 2009)

(untitled)
This paper addresses the empirical question of whether trade and financial openness can help explain the recent pace in financial development, as well as its variation across countries in recent years. Utilising annual data from developing and industrialised countries and dynamic panel estimation techniques, we provide evidence which suggests that both types of openness are statistically significant determinants of banking sector development. Our findings reveal that the marginal effects of trade (financial) openness are negatively related to the degree of financial (trade) openness, indicating that relatively closed economies stand to benefit most from opening up their trade and/or capital accounts. Although these economies may be able to accomplish more by taking steps to open both their trade and capital accounts, opening up one without the other could still generate gains in terms of banking sector development. Thus, our findings provide only partial support to the well known Rajan and Zingales hypothesis, which stipulates that both types of openness are necessary for financial development to take place.